2017
DOI: 10.1530/erc-16-0340
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of the first reported mutations of the proto-oncogene PTTG1IP/PBF

Abstract: Pituitary tumor-transforming gene 1-binding factor (PTTG1IP; PBF) is a multifunctional glycoprotein, which is overexpressed in a wide range of tumours, and significantly associated with poorer oncological outcomes, such as early tumour recurrence, distant metastasis, extramural vascular invasion and decreased disease-specific survival. PBF transforms NIH 3T3 fibroblasts and induces tumours in nude mice, while mice harbouring transgenic thyroidal PBF expression show hyperplasia and macrofollicular lesions. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The following day, Corning BioCoat growth factor reduced Matrigel invasion chambers (Corning; New York, USA) were warmed and rehydrated. Initial experiments evaluated optimum cell density for each line (data not shown), and invasion assays were carried out as we have described previously ( 34 ), before Eosin Y solution (Sigma-Aldrich) staining and being photographed on an EVOS XL Core Imaging System (ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…The following day, Corning BioCoat growth factor reduced Matrigel invasion chambers (Corning; New York, USA) were warmed and rehydrated. Initial experiments evaluated optimum cell density for each line (data not shown), and invasion assays were carried out as we have described previously ( 34 ), before Eosin Y solution (Sigma-Aldrich) staining and being photographed on an EVOS XL Core Imaging System (ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…According to another report, p53 participates in the regulation of mitochondrial and ER interactions, and the knockdown of p53 reduces ER stress-induced injury in mouse cardiomyocytes by protecting mitochondria ( Chen et al, 2019 ). Interestingly, a mutant of PTTG1IP, C51R, was reported to be mainly confined to the endoplasmic reticulum ( Imruetaicharoenchoke et al, 2017 ). PTTG1IP may not be directly related to ER stress, but they may be indirectly involved in ER stress processes due to their close interaction with p53.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that the subcellular localization of PTTG1IP and PTTG1 is crucial for progression of mitosis through the metaphase-anaphase transition (14,15,18). PTTG1IP promotes PTTG1 activation by promoting transfer of PTTG1 from the cytoplasm to the nucleus, thereby allowing the interaction between separase and PTTG1 (50).…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary tumor transforming gene 1 binding factor ( PTTG1IP ; also termed PBF) is a ubiquitously expressed proto-oncogene. PTTG1IP was first identified through its ability to bind to human securin, also termed pituitary tumor transforming gene ( PTTG ) (14,15). Thus far, PTTG1IP has been reported to be highly expressed in thyroid, breast, colorectal, and liver cancer (1619).…”
Section: Introductionmentioning
confidence: 99%